Effect of Substitution Kurisi Fish (Nemipterus sp.) for Milk Fish Satay Production - Bhatara Ayi Meata; Dwi Mulyani; Sakinah Haryati; Aris Munandar; Ginanjar Pratama; Rifki Prayoga Aditia; Afifah Nurazizatul Hasanah; Devi Faustine Elvina Nuryadin (Pusat Unggulan Iptek Ketahanan Pangan Universitas Sultan Ageng Tirtayasa, 2023)
Milkfish satay is a traditional fishery product originating from the Serang area, Banten Province. The main problem with milkfish satay is that the raw material for milkfish is very expensive. Innovation in making milkfish satay can be done by substituting meat from other fish. The purpose of this study was to determine the best formulation of milkfish satay with a combination of milkfish and kurisi fish, and to determine the nutritional content of milkfish satay with a combination of milkfish and kurisi fish. Determination of the best formulation of milkfish satay with the addition of kurisi fish and determining its nutritional value. The formulations tested in the main research were A(100% DB + 0% DK), B(75% DB + 25% DK), C(50% DB + 50% DK), D(25% DB + 75% DK) , E(0% DB + 100% DK). This study was analyzed by organoleptic tests (appearance, color, taste, aroma and texture), proximate (protein, fat, water and ash), microbiology (TPC). Microbiological data were analyzed by means of one-way ANOVA and the organoleptic test was carried out by the Kruskal-Wallis test. If significantly different results were obtained, then Duncan's further test was carried out.